Infection with hepatitis viruses, FIB-4 index and risk of hepatocellular carcinoma in southern Italy: a population-based cohort study. Issue 1 (December 2016) - Fusco, Mario; Piselli, Pierluca; Virdone, Saverio; Di Cicco, Pietro; Scognamiglio, Paola; De Paoli, Paolo; Ciullo, Valerio; Verdirosi, Diana; D'Orazio, Michele; Dal Maso, Luigino; Girardi, Enrico; Franceschi, Silvia; et al.
Abstract Background The incidence of hepatocellular carcinoma (HCC) and its association with hepatitis C (HCV) and hepatitis B virus (HBV) infections, FIB-4 index and liver enzymes was assessed in an area of the province of Naples covered by a population-based cancer registry. Methods We conducted a cohort investigation on 4492 individuals previously enrolled in a population-based seroprevalent survey on HCV and HBV infections. The diagnosis of HCC was assessed through a record linkage with the cancer registry. Hepatic metabolic activity was measured through serum alanine transaminase, aspartate aminotransferase, gamma-glutamyl-transferase, and platelet. The FIB-4 index was used as a marker of fibrosis. We computed HCC incidence rates (IR) for 100, 000 (105 ) person-years of observation, and multivariable hazard ratios (HR) with 95 % confidence intervals (CI) to assess risk factors for HCC. Results Twenty two cases of HCC were diagnosed during follow-up (IR = 63.3 cases/105 ). Significantly increased HCC risks were documented in individuals with higher than normal liver enzymes and low platelet count; in the 239 HCV RNA-positives (HR = 61.8, 95 % CI:13.3–286); and in the 95 HBsAg-positives (HR = 75.0) –as compared to uninfected individuals. The highest FIB-4 score was associated with a 17.6-fold increased HCC risk. Conclusions An elevated FIB-4 index turned out to be an important predictor of HCC occurrence. Although the standard method to assess hepatic fibrosis in chronic hepatitis remains the histologic staging of liver biopsy specimen, the assessment of FIB-4 in HCV RNA-positive individuals may help in identifying the highest HCC-risk individuals who need anti-HCV treatment most urgently.